Clean heating transition in the building sector: The case of Northern China. (20th July 2021) - Tang, Baojun; Zou, Ying; Yu, Biying; Guo, Yangyang; Zhao, Guangpu
Abstract: Currently, more than 70% of the heated floor area in northern China is heated by coal, which severely burdens energy consumption and the environment. Hence, heating in this area is in urgent need of a shift to cleaner approaches. However, current progress is mainly attributed to the generous and unsustainable subsidies of the government, which have become a considerable financial burden. This paper develops a linear recursive dynamic model to identify economical, clean heating pathways in northern China. Different heating demands and clean technology promoting advances are considered. The results show that rapid promotion of clean heating technologies would save 1161–3026 Mtce (million tons of standard coal equivalent) of energy and avoid 7692–8843 Mt CO2, 12–13 Mt CH4, 8–9 Mt SO2 and 7–8 Mt BC emissions cumulatively from 2020 to 2050. For rural residential buildings, biomass pellet furnaces, air source heat pumps and air conditioning should each contribute to about 30% of the heating demands in 2050 to achieve clean heating. However, coal-fired cogeneration should be the major method of coal heating, and mainly serve urban residential buildings and commercial buildings. The consequent energy cost savings of a faster clean heating transition would exceed the increase in investment costs and operational costs. Therefore, promoting clean heating as early as possible is the economical and environmentally friendly choice for northern China in the long run.